Nonhemorrhagic Adrenal Infarction in Pregnancy: Magnetic Resonance Imaging and Computed Tomography Evaluation. Issue 6 (November 2019) - Hynes, Daniel; Jabiev, Azad; Catanzano, Tara
Abstract : Abstract: We present the case of unilateral nonhemorrhagic adrenal infarct in a 29-week pregnant 21-year-old woman. The patient presented with right upper quadrant pain, nausea, and vomiting. Ultrasonography of the right upper quadrant and appendix was negative for pathology. Magnetic resonance imaging of the abdomen demonstrated a right nonhemorrhagic adrenal infarct, subsequently confirmed with limited computed tomography of the upper abdomen. This case discusses the clinical presentation and pertinent imaging findings of adrenal infarction in pregnancy.